Reduced Flow in Delayed Graft Function as Assessed by IVIM Is Associated With Time to Recovery Following Kidney Transplantation. Issue 1 (29th June 2020) - Hashim, Eyesha; Yuen, Darren A.; Kirpalani, Anish
Abstract : Background: Delayed graft function (DGF), defined as the need for dialysis in the first week after kidney transplantation, frequently complicates posttransplantation care. The most common cause of DGF is ischemia–reperfusion injury (IRI). To date, no clinical tools can accurately estimate its severity, nor the time required for recovery of kidney function. Purpose: To investigate if parameters related to directed flow and diffusion of water, as determined by intravoxel incoherent motion diffusion‐weighted imaging (IVIM‐DWI), could be used to differentiate DGF from normal graft function posttransplantation, predict time to recovery from DGF, and hence serve as a surrogate measure of IRI severity. Study Type: Prospective, cross‐sectional cohort study. Population: Fifty consecutive kidney transplant recipients within 3–10 days posttransplantation at our hospital. Field Strength/Sequence: 3.0T/IVIM‐DWI. Assessment: The following IVIM‐DWI parameters were studied: flow‐fraction ( f ), apparent diffusion coefficient (ADC), and total‐ADC ( ADC T ). Mean intrarenal resistive index (R.I.) from Doppler ultrasound was also included for a comparison of IVIM‐DWI with the clinical standard of care. Statistical Tests: Welch's t ‐test, Spearman's correlation, and linear regression. Results: f was significantly reduced in DGF compared to non‐DGF patients in the cortex, medulla, and whole renal parenchyma ( P < 0.05). Time to recovery with respect to MRI correlated negatively with f ( P < 0.05; rho = −0.52 (cortex), and −0.65 [parenchyma]), ADC ( P < 0.05; rho = −0.59 [cortex], 0.59 [medulla], and −0.59 [parenchyma]) and ADC T ( P < 0.05; rho = −0.54 [cortex], and −0.52 [medulla]). Whole renal parenchymal f predicted time to recovery relative to MRI ( P < 0.05, adjusted r‐squared = 0.36). R.I. was significantly different between the groups but did not correlate with time to recovery with respect to MRI (rho = 0.43, P = 0.096). Data Conclusion: Quantification of renal flow using IVIM‐DWI has the potential to serve as a surrogate measure of IRI severity to estimate the degree of and recovery from DGF. Level of Evidence: 2 Technical Efficacy Stage: 3